Manual for magistrates in Newfoundland [electronic resource] : being a guide to their ordinary duties as justices of the peace, with appendix of forms - Prowse, D. W. (Daniel Woodley), 1834-1914. (St. John's, Nfld. : J.C. Withers, 1877)
Includes index. Includes bibliographical references. Electronic reproduction. Mode of access: Internet. 44